Dalmatinska zagora na dlanu - Kusin, Vesna (Array, 2008)
Archaeological finds and sites that tell of the high level of development of civilisation from prehistory to the late Middle Ages, confirm that Zagora achieved cultural unity with other parts of Europe, which is demonstrated in the representative exhibition Dalmatian Zagora – unknown land in Zagreb from 4 September to 18 November 2007. Modern civilisation has for the most part disturbed these areas, but in Zagora, which these processes have happily circumvented, the most preserved prehistoric area in Europe has been maintained, which the modern motorway makes easily accessible. Each period left its impressive cultural and traditional trace in Dalmatian Zagora and this contemporary one confirms that it is an area of great potential, whose sparse soil has given birth to exceptional writers, artists, business people and politicians.